MODERN PEDAGOGICAL AND INFORMATION-COMMUNICATION TEACHING A FOREIGN LANGUAGE USING TECHNOLOGY - Uraimov Sanjarbek; Kuchkarova Yokutkhon; Kochkorova Olimakhon (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The following article devoted to the one of the issues of modern teaching-deeping learning foreign languages and using (them) interactive methods in the process of teaching with the aim of forming knowledge, skills and habits and skills of oral speech among the students.